2014
DOI: 10.1111/mmi.12890
|View full text |Cite
|
Sign up to set email alerts
|

The metabolic regulator CodY links Listeria monocytogenes metabolism to virulence by directly activating the virulence regulatory gene prfA

Abstract: Summary Metabolic adaptations are critical to the ability of bacterial pathogens to grow within host cells and are normally preceded by sensing of host-specific metabolic signals, which in turn can influence the pathogen's virulence state. Previously, we reported that the intracellular bacterial pathogen Listeria monocytogenes responds to low availability of branched-chain amino acids (BCAA) within mammalian cells by up-regulating both BCAA biosynthesis and virulence genes. The induction of virulence genes req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
95
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(100 citation statements)
references
References 95 publications
(145 reference statements)
5
95
0
Order By: Relevance
“…The codY::spc mutation suppressed the virulence defect of the ΔrelAPQ strain to the level of a codY::spc mutation alone, approximately 10-fold less virulent than wild-type (Figure 5B). The virulence defect of the codY::spc mutant is consistent with previous reports demonstrating a virulence defect for a codY mutant (Lobel et al, 2014; 2012), and mutations in codY suppress the virulence defect of other pathogenic Firmicutes with decreased (p)ppGpp (Geiger and Wolz, 2014). Our data suggested that the principle role of (p)ppGpp during infection was the inhibition of GTP synthesis leading to inactivation of CodY.…”
Section: Resultssupporting
confidence: 90%
“…The codY::spc mutation suppressed the virulence defect of the ΔrelAPQ strain to the level of a codY::spc mutation alone, approximately 10-fold less virulent than wild-type (Figure 5B). The virulence defect of the codY::spc mutant is consistent with previous reports demonstrating a virulence defect for a codY mutant (Lobel et al, 2014; 2012), and mutations in codY suppress the virulence defect of other pathogenic Firmicutes with decreased (p)ppGpp (Geiger and Wolz, 2014). Our data suggested that the principle role of (p)ppGpp during infection was the inhibition of GTP synthesis leading to inactivation of CodY.…”
Section: Resultssupporting
confidence: 90%
“…The stringent response is also regulated by the RNA polymerase-binding protein DksA, which regulates amino acid biosynthetic genes as well as antioxidant and antinitrosative defenses essential for Salmonella pathogenesis (Henard and Vazquez-Torres, 2012; Henard et al, 2014). In Gram-positive bacteria, CodY is involved in regulating virulence gene expression in response to amino acid availability (Geiger et al, 2010; Lobel et al, 2015). In Listeria , CodY induces expression of the virulence regulator PrfA when concentrations of branched-chain amino acids are low, while its role in S. aureus virulence gene regulation is more complex.…”
Section: Stresses In the Host Environmentmentioning
confidence: 99%
“…Consequently, an L. monocytogenes codY mutant is impaired in motility and intracellular replication (35, 39). The role of CodY during L.…”
Section: Bcaas At the Crossroads Of Metabolism And Virulencementioning
confidence: 99%